2017
DOI: 10.1007/s00442-017-3938-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and nitrogen resorption from different chemical fractions in senescing leaves of tropical tree species on Mount Kinabalu, Borneo

Abstract: Nutrient resorption, a process by which plants degrade organic compounds and resorb their nutrients from senescing tissues, is a crucial plant function to increase growth and fitness in nutrient-poor environments. Tropical trees on phosphorus (P)-poor soils are particularly known to have high P-resorption efficiency (PRE, the percentage of P resorbed from senescing leaves before abscission per total P in green leaves). However, the biochemical mechanisms underlying this greater PRE remain unclear. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 51 publications
2
49
3
Order By: Relevance
“…Furthermore, we found that P green had negative effects on PRE, which is supported by the findings by Kobe et al [59]. Green leaf nutrient status is supposed to represent soil nutrient availability, whose negative impacts on nutrient resorption efficiency is widely accepted [41,59,60]. Therefore, green leaf nutrient status may negatively relate to nutrient resorption efficiency.…”
Section: Controls Of Nutrient Resorption In Planted Forestssupporting
confidence: 85%
“…Furthermore, we found that P green had negative effects on PRE, which is supported by the findings by Kobe et al [59]. Green leaf nutrient status is supposed to represent soil nutrient availability, whose negative impacts on nutrient resorption efficiency is widely accepted [41,59,60]. Therefore, green leaf nutrient status may negatively relate to nutrient resorption efficiency.…”
Section: Controls Of Nutrient Resorption In Planted Forestssupporting
confidence: 85%
“…; Marschner , Tsujii et al. ), and which are highly soluble in the phloem sap, generally have high remobilization rates. But, like most biological processes, nutrient remobilization is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…This non‐linear response may be due to the fact that nutrients are in different pools that are not equally available and consequently do not require the same energy to be remobilized (Tsujii et al. ). Indeed, the remobilization process implies the reuse of nutrients stored in vacuoles (amino‐N, P, K, Mg), but can also imply the breakdown of storage proteins or cells structures (chloroplasts, Mg; enzymes, N; micronutrients; Marschner ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was designed for investigating altitudinal patterns of nutrient resorption efficiency resulting from adaptation of individual species to changes in soil nutrient status across the gradient. Patterns of nutrient resorption across environmental gradients are often determined by changes in species composition (Achat et al, ; Richardson et al, ; Tsujii, Onoda, & Kitayama, ). In order to prevent confounding effects of compositional turnover across the altitudinal range, we selected species that occurred with high frequency across a broad altitudinal range on two bedrock types.…”
Section: Introductionmentioning
confidence: 99%